2007
DOI: 10.1177/155005940703800306
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing a Mother's Voice in the Persistent Vegetative State

Abstract: We studied an 8-year-old boy after a near-drowning left him in a vegetative state (VS) for 4 years before the study. Findings fulfilled all clinical criteria for the diagnosis of VS. The purpose of this study was to investigate whether there was significant differential activation of the brain in response to hearing his mother's voice compared with the voices of unknown women. The data were assessed using quantitative electric tomography (QEEGt), a technique that combines anatomical information of the brain by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 22 publications
(22 reference statements)
0
42
0
Order By: Relevance
“…This finding was Page 9 replicated by Perrin et al (2006) in 3 out of 5 VS patients, all 6 MCS patients, 4 LIS patients, and 5 healthy controls. Machado et al (2007) observed oscillatory changes in the gamma band in a boy in VS when he listened to his mother's voice, but not when the same words were spoken by unfamiliar women. In the only substantial group study of emotion in DOC, Kotchoubey et al (2009) examined patients' ERP responses to woeful exclamations as oddball stimuli in a series of joyful stimuli (single words in which only the prosody determined the emotion).…”
Section: Familiarity and Emotionmentioning
confidence: 88%
“…This finding was Page 9 replicated by Perrin et al (2006) in 3 out of 5 VS patients, all 6 MCS patients, 4 LIS patients, and 5 healthy controls. Machado et al (2007) observed oscillatory changes in the gamma band in a boy in VS when he listened to his mother's voice, but not when the same words were spoken by unfamiliar women. In the only substantial group study of emotion in DOC, Kotchoubey et al (2009) examined patients' ERP responses to woeful exclamations as oddball stimuli in a series of joyful stimuli (single words in which only the prosody determined the emotion).…”
Section: Familiarity and Emotionmentioning
confidence: 88%
“…For example, a study conducted on an 8-year-old boy who nearly drowned and was left in a vegetative state for 4 years prior to the study demonstrated that there were significant differential activations in EEG frequencies at 14-58 Hz, with specific brain activity at 33.2 Hz (gamma band) to the sound of his mother's voice when compared with the voices of unfamiliar women. 20 An additional study analyzed electrophysiological data on how newborns process their mother's voice compared with the voice of a stranger and found that exposure to one's maternal voice elicited early language-relevant processing, whereas the stranger's voice elicited more voice- specific responses. 21 In an experiment examining eventrelated potentials to audio of a subject's own name (SON) recorded by a familiar voice vs. an unknown voice that was recorded by an unfamiliar person, the SON elicited large response amplitudes during the later phase of a novel P3 (after 300 ms).…”
Section: Discussion Presentation Order Effectsmentioning
confidence: 99%
“…Additionally, for subsequent analyses, the b band (13-30 Hz) was divided into its two respective portions: b1 band (13-20 Hz) and b2 band (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Subsequent comparisons examining the content ratios within the four sites (F3, F4, C3 and C4) revealed a significant increase in brain activity while listening to a familiar voice (a mother's voice) specifically in the b1 band at the F4 site (Fig.…”
Section: Comparison Between Familiar and Unfamiliar Voices Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed no evidence of gestural or verbal communication, no ability to follow commands, and no visual pursuit, or purposeful motor behavior, fulfilling PVS diagnostic criteria. [2][3][4][5][6][7][8][9][10] Auditory, visual, motor, oromotor, communication, and arousal processes were assessed in all cases by the JFK scale, 22 ranging from 3 and 6 points.…”
Section: Methodsmentioning
confidence: 99%